2003
DOI: 10.1111/j.1365-2621.2003.tb05747.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flour Quality, Ascorbic Acid, and DATEM on Dough Rheological Parameters and Hearth Loaves Characteristics

Abstract: The effects of protein quality, protein content, ascorbic acid, diacetyl tartaric acid ester of monoglycerides (DATEM), and their interactions on dough rheology and hearth bread properties were studied by sizeexclusion fast protein liquid chromatography, Kieffer Dough & Gluten Extensibility Rig, and small-scale baking of hearth loaves. The effect of protein content was either positive or negative on hearth loaf characteristics, form ratio, and area, depending on the amount of the largest glutenin polymers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Preliminary studies at the Grain Research Laboratory (data not shown) with a range of Canadian flours confirmed the importance of proper dough development and the requirement for ascorbic acid at levels of about 40 ppm for optimum bread quality, consistent with previous studies of hearth bread quality (Grandvoinnet and Berger 1979;Faergestad et al 2000;Aamodt et al 2003). Oven temperature control and the control of steam added during the first few minutes were also critical to obtaining reproducible results.…”
Section: Preliminary Studiessupporting
confidence: 61%
See 1 more Smart Citation
“…Preliminary studies at the Grain Research Laboratory (data not shown) with a range of Canadian flours confirmed the importance of proper dough development and the requirement for ascorbic acid at levels of about 40 ppm for optimum bread quality, consistent with previous studies of hearth bread quality (Grandvoinnet and Berger 1979;Faergestad et al 2000;Aamodt et al 2003). Oven temperature control and the control of steam added during the first few minutes were also critical to obtaining reproducible results.…”
Section: Preliminary Studiessupporting
confidence: 61%
“…Studies have shown that these characteristics can normally be achieved in hearth breads through the choice of flour with the appropriate strength properties and protein content (Dexter et al 1985, Faergestad et al 2000 and by manipulation of processing parameters with emphasis on proper dough development and fermentation (Grandvoinnet and Berger 1978, Dogan et al 1996, Faergestad et al 2000. For lean formula hearth breads, additives such as ascorbic acid and surfactants can also strongly influence bread properties (Grandvoinnet and Berger 1979;Aamodt et al 2003).…”
mentioning
confidence: 99%
“…Three redox agents are used to selectively alter gluten network formation during production of laminated dough. Ascorbic acid (AA), widely used as flour improver, increases dough strength and reduces its stickiness (Aamodt et al, 2003). Potassium iodate (KIO 3 ), a fast-acting oxidizing agent, impacts the dough thiol-SS system and can thus affect glutenin subunit polymerization (Joye et al, 2009) thereby increasing dough strength.…”
Section: Introductionmentioning
confidence: 99%
“…The PCs are used as new axes in a plot of samples (score plot) and a corresponding plot of variables (loading plot). This makes it possible to get an overview of the data and to find which properties are related, and which properties are most important in distinguishing between samples (Aamodt et al, 2003). All variables were scaled to unit variance before analysis, and cross-validation was used for evaluation of the model.…”
Section: Discussionmentioning
confidence: 99%
“…This method projects the information in the original intercorrelated variables onto a small number of new variables, called principal components (PCs) (Aamodt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%